International Development 2014
DOI: 10.1093/acprof:oso/9780199671656.003.0042
|View full text |Cite
|
Sign up to set email alerts
|

South Africa's Quest for Inclusive Development

Abstract: The end of apartheid in 1994 ushered in a new era in South Africa and with it came the challenge of building a democratic, inclusive and stable society. The government led by the African National Congress initially followed a neoliberal stance to manage the economy and a redistributive strategy to close the income disparity with a streak of a developmental state. These two tracks were at times at odds with each other. The last decade has shown widening inequality and slow progress in addressing poverty, depriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Entrepreneurship for job creation has been documented as one of the important remedies for Africa's growing population and, thus, reducing unemployment and poverty (Tchamyou, 2016). Unemployment among youth in Africa, especially Sub-Saharan Africa, has remained high (Jauch, 2011;Ncube et al, 2014) thus compelling unemployed youth to venture into self-employment in the informal sector (Chigunta, 2017). Therefore, entrepreneurship is increasingly becoming important around the world (Movahedi, Fathi, & Brijal, 2011) and is particularly true in emerging economies where unemployment levels are high.…”
Section: Entrepreneurship and Its Importancementioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneurship for job creation has been documented as one of the important remedies for Africa's growing population and, thus, reducing unemployment and poverty (Tchamyou, 2016). Unemployment among youth in Africa, especially Sub-Saharan Africa, has remained high (Jauch, 2011;Ncube et al, 2014) thus compelling unemployed youth to venture into self-employment in the informal sector (Chigunta, 2017). Therefore, entrepreneurship is increasingly becoming important around the world (Movahedi, Fathi, & Brijal, 2011) and is particularly true in emerging economies where unemployment levels are high.…”
Section: Entrepreneurship and Its Importancementioning
confidence: 99%
“…Botswana, as most of the other middle-income countries in southern Africa, has been among the slow growing economies grappling with high unemployment, especially youth unemployment which has remained elusive (Jauch 2011;Ncube, Shimeles, & Verdier-Chouchane, 2014). Although the country promotes entrepreneurship, the labour market is characterized by high and increasing unemployment rate which has consistently been a 2-digit figure averaging 18.2% between 2000(Morima, 2012Matandare, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With high unemployment and youth unemployment, inclusive growth in the region has remained elusive (Jauch 2011;Ncube et al 2014). Despite the oversized public sectors, overall employment has been low, reflecting limited private sector job creation and entrepreneurship, both in the formal and informal sectors.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars argued that the economic trend that is prevalent in African is strongly dependent on investments in new technology, hightechnology industries, and skilled labor, which are essential ingredients for the development of a knowledge-based economy (Tchamyou, 2016). Additionally, literature showed that the growing unemployment rate would be mostly accommodated by the entrepreneurship from the private sector which exceeds 50% of the young labor force and remains among the highest in Africa (Brixiova, Ncube, & Bicaba;Ncube, Shimeles, & Verdier-Chouchane, 2013). The promises are that the promotion of knowledge-based entrepreneurship holds high potential for the improvement and development of other sectors such as that of agriculture, water and energy, and technology (Tchamyou, 2016).…”
Section: The Promise and Challenge Of Diffusion Of Innovation In Sub-mentioning
confidence: 99%